2020
DOI: 10.34105/j.kmel.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Examining university students’ attitudes towards using web-conferencing systems in distance learning courses: A study on scale development and application

Abstract: The study aimed to develop a scale to assess students’ attitudes towards using interactive web conferencing systems in distance learning courses. An item pool was formed based on a review of the literature and the participants’ written views. A draft scale was developed with 29 items selected from this item pool. It was applied to 1100 undergraduate students in a distance program in theology, who took courses using Adobe Connect as a video conference system, together with Moodle as a learning management system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…It is known that both educators and university students will change positively when appropriate methods and techniques are used in the research, and this provides benefits and contributions to the field [16]. Basaran et al (2020) aimed to evaluate the attitudes of university students towards using interactive web conferencing systems in distance education courses, and they continued to work on adobe connect. They concluded that they are the user preference for the web conferencing system [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that both educators and university students will change positively when appropriate methods and techniques are used in the research, and this provides benefits and contributions to the field [16]. Basaran et al (2020) aimed to evaluate the attitudes of university students towards using interactive web conferencing systems in distance education courses, and they continued to work on adobe connect. They concluded that they are the user preference for the web conferencing system [5].…”
Section: Resultsmentioning
confidence: 99%
“…Basaran et al (2020) aimed to evaluate the attitudes of university students towards using interactive web conferencing systems in distance education courses, and they continued to work on adobe connect. They concluded that they are the user preference for the web conferencing system [5]. In this context, among the results of the research, it is seen that there are positive answers about the adobe connect application, it is known that the adobe connect application is preferred among many platforms because it makes students feel like they are in their own classroom environment, it is thought that the adobe connect platform benefits university students among distance education applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Byun and Slavin (2020) conclude that the pandemic has brought both challenges and benefits to the educational system; while distance e-learning is likely to reduce the quality of education, in return it is considered an opportunity to improve educational content and professional development for teachers. Although online learning environments aim to introduce learning to students with the help of synchronous web conferencing tools, slides, files, and various applications (Basaran & Yalman, 2020). Utomo et al (2020) suggest that no single tool can meet all the needs for distance learning assignments, exams, discussions and face-to-face meetings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thanks to web conferencing technologies, academic faculty members can manage and upload educational content in the form of presentations, image files and documents, publish live video content using a webcam, and share screen and audio with students. Students can interact with each other and with faculty members, share information, and use instant messaging to ask questions (Basaran & Yalman, 2020), using this technology effectively in online learning. The sense of group belonging among learners may replace face-to-face classroom learning to some extent (Jena, 2020), because e-learning systems provide tools to interact with them and with other students through discussion and comment forums.…”
Section: Literature Reviewmentioning
confidence: 99%